Environmental-friendly food products’ packaging: women’s purchasing preferences - Kamaruddin, Norfaryanti; Mohd Razali, Sheriza; Samdin, Zaiton (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Plastic pollution is a recent global issue. Its utilisation has increased tremendously in all aspects of life. Marine wildlife is a major threat group. As a result of these environmental degradation caused by plastics, there are various effort to manage it sustainably. This includes innovation in plastic-based product packaging. There are increasing interests in the field of ethical/responsible consumption as many campaigns are driving the environmentally-friendly consumerism. This paper is focusing on explaining women’s purchasing preference in the environmental-friendly product packaging. Cross-sectional data were collected through a web-based survey. The research population consisted of women consumers who are working in Klang Valley, Malaysia. A three-part questionnaire was used as an instrument; demographic profiles, purchasing patterns and purchasing preference. Only 3.5% of respondents preferred to buy grocery items made from environmental-friendly packaging materials. This result complicates the food packaging waste pollution problems, as 70% of the purchasing of the grocery items is made on a weekly basis which will intensify the non-biodegradable plastic pollution problems.